Prenatal arsenic exposure, child marriage, and pregnancy weight gain: Associations with preterm birth in Bangladesh. (March 2018) - Rahman, Mohammad L.; Kile, Molly L.; Rodrigues, Ema G.; Valeri, Linda; Raj, Anita; Mazumdar, Maitreyi; Mostofa, Golam; Quamruzzaman, Quazi; Rahman, Mahmudur; Hauser, Russ; Baccarelli, Andrea; Liang, Liming; et al.
Abstract: Background: Preterm birth is a disease of multifactorial etiologies that has environmental, social, and maternal health components. Individual studies have shown that exposure to arsenic contaminated drinking water, child marriage, and low maternal weight gain during pregnancy contribute to preterm birth. These factors are highly prevalent and often co-exist in Bangladesh, a country in South Asia with one of the world's highest prevalences of preterm birth. Objective: To evaluate the individual and interactive effects of prenatal arsenic exposure, child marriage, and pregnancy weight gain on preterm birth in a prospective birth cohort in Bangladesh. Methods: During 2008–2011, we recruited 1613 pregnant women aged ≥ 18 years at ≤ 16 weeks of gestation and followed them until 1-month post-partum. We measured total arsenic in drinking water (n = 1184) and in maternal toenails (n = 1115) collected at enrollment and ≤ 1-month post-partum, respectively using inductively coupled plasma mass spectrometry. Child marriage (< 18 years old) was defined using self-report, and 2nd and 3rd trimester pregnancy weight gain was calculated using monthly records. Gestational age was determined at enrollment by ultrasound. Results: In multivariate adjusted Poisson regression models, the risk ratios (RR) for preterm birth were 1.12 (95% CI: 1.07–1.18) for a unit change in natural log water arsenic exposure, 2.28 (95% CI: 1.76–2.95) for child marriage, and 0.64 (95% CI: 0.42–0.97) for a pound per week increase in maternal weight during the 2nd and 3rd trimesters. In stratified analysis by child marriage, pregnancy weight gain was inversely associated with preterm birth among women with a history of child marriage (RR = 0.58; 95% CI: 0.37–0.92), but not among women with no history of child marriage (RR = 0.86; 95% CI: 0.37–2.01). Mediation analysis revealed that both arsenic exposure and child marriage had small but significant associations with preterm birth via lowering pregnancy weight gain. Similar associations were observed when arsenic exposure was assessed using maternal toenail arsenic concentrations. Conclusions: Reducing arsenic exposure and ending child marriage could reduce the risk of preterm birth in Bangladesh. Furthermore, enhancing nutritional support to ensure adequate weight gain during pregnancy may provide additional benefits especially for women with a history of child marriage. Highlights: In Bangladesh, the prevalence of preterm birth is very high. Common risk factors are arsenic exposure, child marriage & perinatal undernutrition. Arsenic exposure & child marriage are associated with higher risk of preterm birth. Pregnancy weight gain is associated with lower risk of preterm birth. Adequate nutrition among women with a history of child marriage is important.